2009
DOI: 10.1152/ajpendo.00282.2009
|View full text |Cite
|
Sign up to set email alerts
|

A highly energetic process couples calcium influx through L-type calcium channels to insulin secretion in pancreatic β-cells

Abstract: Jung SR, Reed BJ, Sweet IR. A highly energetic process couples calcium influx through L-type calcium channels to insulin secretion in pancreatic ␤-cells. Am J Physiol Endocrinol Metab 297: E717-E727, 2009. First published July 7, 2009 doi:10.1152/ajpendo.00282.2009 ) influx is required for the sustained secretion of insulin and is accompanied by a large rate of energy usage. We hypothesize that the energy usage reflects a process [Ca 2ϩ /metabolic coupling process (CMCP)] that couples Ca 2ϩ to insulin secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 50 publications
(75 reference statements)
3
48
0
Order By: Relevance
“…-Cytosolic Ca 2ϩ was measured by fluorescent imaging of islets after loading them with Fura-2 AM (Invitrogen) as described previously (28). Dyed islets were pipetted into a temperature-controlled perifusion dish as a monolayer (Bioptechs, Butler, PA) that was mounted onto the stage of a Nikon Eclipse TE-200 inverted microscope, and fluorescent emission was detected at 510 nm during alternating excitation at either 340 nm or 380 nm.…”
Section: Imaging and Quantification Of Cytosolic Ca 2ϩmentioning
confidence: 99%
See 2 more Smart Citations
“…-Cytosolic Ca 2ϩ was measured by fluorescent imaging of islets after loading them with Fura-2 AM (Invitrogen) as described previously (28). Dyed islets were pipetted into a temperature-controlled perifusion dish as a monolayer (Bioptechs, Butler, PA) that was mounted onto the stage of a Nikon Eclipse TE-200 inverted microscope, and fluorescent emission was detected at 510 nm during alternating excitation at either 340 nm or 380 nm.…”
Section: Imaging and Quantification Of Cytosolic Ca 2ϩmentioning
confidence: 99%
“…We have previously established that Ca 2ϩ , along with cytochrome c signaling, co-stimulate a highly energetic process, the CMCP, whose activation is essential for stimulating ISR. This is based on observations that the glucose dose response of the CMCP is superimposable to that of ISR (12), the CMCP is blocked by an inhibitor of Ca 2ϩ -dependent kinases (15), and like ISR, the CMCP is only activated when both the reductive state of cytochrome c, and the activity of L-type Ca 2ϩ channels, are increased (11). In the present study, Ca 2ϩ -sensitive OCR was completely absent in the islets precultured in low glucose and quantitatively restored with the GKa.…”
Section: Relative Control Of Isr By Ca 2ϩmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that Ca 2ϩ -sensitive OCR reflects a highly energetic process that couples Ca 2ϩ to the secretion of insulin (6). In lieu of the identification of the proteins involved with this process, we termed this process the Ca 2ϩ /metabolic coupling process (CMCP) (24). Further studies revealed that potentiation of the insulin secretion rate (ISR) by protein kinase C (PKC) and cAMP-dependent pathways occur with only very small changes in OCR, demonstrating that activation of insulin secretion by these mechanisms is mediated by steps that are downstream of the CMCP (6).…”
mentioning
confidence: 99%
“…The potent effect of Ca 2+ influx on oxygen consumption rate reflect an essential downstream and highly energetic process that couples Ca 2+ influx through L-type Ca 2+ channel with insulin secretion rate with the process Ca 2+ /metabolic coupling process (CMCP) 13 . Ascorbic acid (vitamin C) is a natural antioxidant, it can play a very important role in cell proliferation by scavenging free radicals.…”
Section: Discussionmentioning
confidence: 99%